Produção de Alimentos em Goiás: impasses entre commodities, agricultura de base camponesa e a globalização dos hábitos alimentares - Lara Cristine Gomes Ferreira; Caio César Alencar de Sena (Confins)
This article analyzes food production in Goiás, considering the impasses between the production of commodities and the production of peasant-based food, as well as the current effects of the globalization process of eating habits. It also aims to reflect and outline an overview of the globalization process, the construction of new eating habits and complex social problems such as the population's obesity. The research methodology involved documentary research in secondary databases, bibliographic review, analysis based on reflections and critical bibliographies, as well as presentation of graphs and tables with synthesis of data from different sources. The combination of data on food, health and economics suggests correlations and possibilities to reflect the complexity and consequences of recent changes in eating habits driven by globalization; which has an impact not only on the economy but also on health and points to the need to rethink paths based on a cultural consumption of food. As results of the article, it should be noted that, although investments in agriculture have increased exponentially in Goiás, this resource is mainly focused on the complex grains, meat and biofuels, that is, on the agro-export market. For fruit and vegetable production, the largest production is in the Metropolitan Region of Goiânia or in the vicinity of medium and large cities such as Anápolis and around Brasília. It was noted that the state of Goiás is still a long way from building an alternative food system to the hegemonic model. Globalization has increasingly expanded fast food and food corporations are expanding the production of industrialized and ultra-processed foods, which consequently raises the rates of obesity and other health problems, as well as increasingly distancing the collective construction of food sovereignty.